Analisis Tingkat Partisipasi Masyarakat Dalam Pembangunan Desa, di Desa Canggu Kecamatan Kuta Utara Kabupaten Badung - I Wayan Martha Wijaya Kusuma; A. A. Gde Raka; I Made Sumada (Public Inspiration: Jurnal Administrasi Publik, 2022)
Development supports every nation and state to achieve a better level of life, as is the case with the State of Indonesia in the fourth paragraph of the Preamble of the 1945 Constitution which was formulated by the founders of the Unitary State of the Republic of Indonesia that the aim of the National Development of the Indonesian Nation is to protect the Indonesian nation and its blood. from all over Indonesia and to advance the general public, educate the nation's life and participate in implementing world welfare. This study aims to determine the level of community participation in development in Canggu Village, North Kuta District, Badung Regency. The location of this research is Canggu Village, North Kuta District, Badung Regency. The population in this study was Canggu Village Government Apparatus who found 27 people. The theory used in this research is Uceng's participation theory; (2019). The sampling technique used is purposive sampling, the data collection method used is the method of observation, interviews and documentation. The data analysis technique used is descriptive qualitative. The results of this study indicate that community participation in Canggu Village is still not maximized. The factors that have not been maximized in Canggu Village are caused by the lack of development active community participation. The impact obtained from community participation in village development has not been maximized, namely the results obtained in development are not optimal and are not in accordance with the needs and conditions of Canggu Village.